(3cJGH GdEeGe jMji Hf MeRI Edi Gdabjg eSYhO Hf eMeO GdMhjJ Hfbd CehGd GdeSGLO HYVgG Edi HYV hcJH CNQi dgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3jMi Hf GdgGOi Hf CejQ GdeDefjf s)
(3ChdgG (B:s
(3QCjfG hQCi BHGDfG Ydjge GdSdGe GdYed Ydi GdESJUdGM GdeQSd eeG cGf LGQjkG Ydi CUhd GdTQjYI s
(3BNQgG (B:s
(3dG jdhi Ydi TF JbQHkG Edi Gddg JYGdi(B"(3, hGeJKGdkG dCeQg ai Pdc HJGQjN s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds